Dinasti Mamluk: Dari Prajurit Budak ke Penguasa Mesir dan Suriah - Nadhifah, Naura (Maliki Interdisciplinary Journal, 2025)
The Mamluk dynasty was a dynasty founded by slaves. This dynasty was one of the strongest dynasties in the history of Islamic civilization. This study aims to, 1) Find out how the slave-based military system could lead the Mamluks to become rulers in Egypt and Syria, 2) What factors allowed them to maintain power in Egypt and Syria. This research is a qualitative study with a literature study approach. Research data was taken from primary sources such as articles, books, journals, and research reports related to the Mamluk dynasty. The results of the study show that, 1) The military system implemented by the Mamluks was very unique, namely a slave-based military. The military was selected and educated and trained intensively from a young age, then instilled in them Islamic values ​​so that they grew into disciplined and loyal soldiers. Another advantage of them was their ability to move in all fields. 2) The main factors that allowed the Mamluks to maintain their power were a unique and efficient military structure, economic stability based on trade control, religious legitimacy, diplomatic intelligence, supportive social structure, and the existence of culture and architectural heritage